Perspectives of integration of educational disciplines «Informational Networks and Systems» and «Bibliology» for students of specialty 51.03.06 Library and Information Activities - J. V. Gushul; A. V. Mikhailova (Открытое образование (Москва), 2016)
The purpose of research - to find ways to optimize and modernize the educational process of high schools of culture based on the active introduction of information technology and the integration of the disciplines of library profession. This article describes an innovative integration project in two disciplines - «Informational Networks and Systems» and «Bibliography», which is a lab to create a site on the specific theme.It should be revealed how interdisciplinary integration project increases the efficiency of the educational process, provides enhanced knowledge, shows the possibility of their practical use and, more importantly, allows you to simulate the information environment and develop skills for the implementation of the integrative function in the future professional activity. Materials and Methods: Analysis of educational-methodical documentation showed the possibility of interdisciplinary work.Disciplines are complementary and provide conditions for sharing of practical and laboratory results that enriches disciplines and outputs library education to a new level of interdisciplinarity, the modeling of the information environment of the future professional activity, increasing students responsibility for their work on the basis of introduction of information technologies.The method of observation revealed and substantiated methodological solutions in the organization of the laboratory work on the discipline «Information systems and networks»: use developments of the discipline «Bibliography», improve the efficiency of search and extraction of information in the global information space, to start with site design, dedicated to a specific person, use developing a software like site builder, etc.The analysis of the first results showed the problematic integration of the field: unwillingness of students-future librarians to take responsibility for the quality of the work itself, increasing labor costs of teachers, enhancing the personality of the teacher in the educational process, a significant strengthening of the role of independent work students and their unwillingness to her and others.Results: the first experience of the implementation of the integration project analyzed by the students, proposed methodological solutions for the implementation of an interdisciplinary project. The use of the offered service based on the site builder described in detail. Analyzed its possibilities: layout choices, themes, host to host, the connection widgets, posting links to other resources, etc. - for the acquisition of information technology-librarians students. It emphasized the possibility of further development resulting in the classroom for discipline «Information systems and networks» project «site specific person» in the foreign exchange in other disciplines and final qualifying work. Seen and identified problem areas of modern educational process: the difficulty in understanding of information technology to the current level of library specialties entrants, the reluctance of students to be responsible for the result and the inability to manage their own independent work and others.Conclusion: The urgency of the integration of interdisciplinary project and its compliance with the new educational paradigm - the modeling of the information environment of the future professional activity. In this crucial implementation of information technology in education and research work of students. The integration project is implemented in the Institute of Culture when preparing future librarians.